2006
DOI: 10.1002/gps.1706
|View full text |Cite
|
Sign up to set email alerts
|

The effect of community based daycare on mental health and quality of life of elderly in rural south India: a community intervention study

Abstract: Forty-one (16.4%) were invited to take part. Twenty subjects took part in the program while 21 refused. There was a significant reduction in psychiatric morbidity and improvement in quality of life scores at 3 months for subjects who attended the program. The improvement in quality of life persisted after adjusting for gender, socioeconomic status and baseline scores. Costing of the program suggests sustainability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 3 publications
0
38
0
2
Order By: Relevance
“…Nevertheless, around a fifth of people with dementia (10–37% by centre) live alone or with a spouse only, and hence can be considered vulnerable 207,218. Current research indicates that a worryingly high proportion of people with dementia lack the basic necessities for life (ie, food), particularly in parts of Latin America, and in India, where social protection is most insecure 4,205,207,209,210,218,219…”
Section: Dementia Awareness Care and Servicesmentioning
confidence: 99%
“…Nevertheless, around a fifth of people with dementia (10–37% by centre) live alone or with a spouse only, and hence can be considered vulnerable 207,218. Current research indicates that a worryingly high proportion of people with dementia lack the basic necessities for life (ie, food), particularly in parts of Latin America, and in India, where social protection is most insecure 4,205,207,209,210,218,219…”
Section: Dementia Awareness Care and Servicesmentioning
confidence: 99%
“…Very few studies had been conducted to assess the QOL among elderly in India [3,4]. Many studies were conducted on QOL among elderly in other countries [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is similar with prior study that reported that independence in ADL had a positive impact on health perception and health‐related quality of life in elderly stroke patients (Ytterberg et al., ). Medical and nursing services provided in ADCs improved quality of life and psychological health of older people (Jacob et al., ). Therefore, our findings support those of prior studies in which ADC services that provided health management improved psychological health, particularly perceived health and quality of life, of the elderly with stroke who used an ADC.…”
Section: Discussionmentioning
confidence: 99%
“…The social services also included staff assistance in reminding patients to take their medications. In addition to the usual ADC services, our intervention program incorporated two new key components: (1) family involvement in the elderly stroke patients' care and (2) patient‐tailored health management—both of which were developed from previous research findings in which family involvement and health management improved health and psychological outcomes of the elderly or their caregivers (Jacob, Abraham, Abraham & Jacob, ; Park, ; Ross, Carswell & Dalziel, ). The 12‐week intervention was conducted in the ADC by a master's‐prepared registered nurse (RN) assisted by a physical therapist.…”
Section: Methodsmentioning
confidence: 99%